2016
DOI: 10.1590/1678-4324-2016150136
|View full text |Cite|
|
Sign up to set email alerts
|

Blackberry Vinegar Produced By Successive Acetification Cycles: Production, Characterization And Bioactivity Parameters

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 28 publications
3
21
1
Order By: Relevance
“…These authors found a total phenolic compound content of 816 mg GAE/100 g and 750.5 mg GAE/100 g in the Powder Blue and Delite varieties, respectively. Solvents with different polarity have been used for the extraction of polyphenolic compounds from fruits, such as acidified methanol, ethanol, acidified ethanol, acetone and acidified acetone (CUNHA et al, 2016). As also observed in the present work, Cunha et al (2016) verified that acetone was 73.1% more efficient in extracting phenolic compounds (1.702 mg GAE/100 g) than ethanol (983.4 mg GAE/100 g) in samples of Brazilian blackberries.…”
Section: Physicochemical Characterization and Determination Of The Bisupporting
confidence: 84%
See 4 more Smart Citations
“…These authors found a total phenolic compound content of 816 mg GAE/100 g and 750.5 mg GAE/100 g in the Powder Blue and Delite varieties, respectively. Solvents with different polarity have been used for the extraction of polyphenolic compounds from fruits, such as acidified methanol, ethanol, acidified ethanol, acetone and acidified acetone (CUNHA et al, 2016). As also observed in the present work, Cunha et al (2016) verified that acetone was 73.1% more efficient in extracting phenolic compounds (1.702 mg GAE/100 g) than ethanol (983.4 mg GAE/100 g) in samples of Brazilian blackberries.…”
Section: Physicochemical Characterization and Determination Of The Bisupporting
confidence: 84%
“…Although several studies in the scientific literature have described the antioxidant potential of different fruits, there are few reports on the antioxidant capacity of fruit vinegars (CUNHA et al, 2016). The results of the in vitro antioxidant activity assays (Tables 2 and 3) showed that both the in natura blueberry fruit, and the wine and vinegars produced from them, presented high antioxidant capacity.…”
Section: Determination Of the Antimicrobial Activity Of Blueberry Vinmentioning
confidence: 97%
See 3 more Smart Citations